PENGETAHUAN AKUNTANSI LINGKUNGAN, KEPEKAAN LINGKUNGAN, DAN PENGETAHUAN CSR TERHADAP KEBERLANJUTAN LINGKUNGAN MAHASISWA AKUNTANSI DI KOTA BATAM - Vincent Fredly; Argo Putra Prima (LPPM Universitas Putera Batam, 2026)
Environmental sustainability has become an important issue in accounting due to the increasing environmental impacts of economic activities. Accounting students, as future professionals, are expected not only to master technical accounting skills but also to understand environmental issues and corporate social responsibility. This study aims to analyze the effect of environmental accounting knowledge, environmental sensitivity, and Corporate Social Responsibility (CSR) knowledge on the environmental sustainability of accounting students in Batam City. This research uses a quantitative approach with a survey method. The research population consists of final-year accounting students at universities in Batam City, and the sampling technique used is purposive sampling. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression analysis after conducting data quality tests and classical assumption tests. The results show that environmental accounting knowledge, environmental sensitivity, and CSR knowledge partially have a positive and significant effect on the environmental sustainability of accounting students. In addition, the three independent variables simultaneously have a significant effect on the environmental sustainability of accounting students in Batam City. The conclusion of this study is that improving environmental accounting knowledge, environmental sensitivity, and CSR knowledge can enhance sustainability awareness and attitudes among accounting students. This study is expected to provide useful input for higher education institutions in developing sustainability-oriented accounting education.